Environmental effects of private generators in the city of Baghdad - Hadi, Safaqes qassim (Al-Adab Journal, 2022)
The electric energy is considered as nerve of life in the life of cities, so every country can’t improve and precede without electric energy services. The progress in industry and technology are enable to improve without electricity services, especially advancement countries. Iraq is from growing that suffer from shortage in national electric energy services because of the big increasing of population electric energy production which leaves to increasing in demand on electric energy production. On the other hand, the stations that general electricity are old and break down from time to time but after , 1990, the as a result of the wars and the conditions of the economic blockade led Destruction of infrastructure and prevention of import of repair tools for electric stations, and after 2003 the powerlessness happens in generation sector for national station , that happens because of the war and robberies , Therefore, the dependence on native generators which work (diesel), appeared after the powerlessness reaches to (52%) in national nets all over of Iraq. In Baghdad Governorate, and as a result of the increase in population and the sharp rise in temperatures compared to the large deficit in the national energy networks, all of this led to an increase in the demand for electrical energy. The native generators became a popular in the streets, roads and shops of Baghdad, and these generators are the basis to generate electricity. Because of the large number of generators, the pollution spread in air and soil in Baghdad. These generators produce many gases like, Co2, No2, So2, and other pollutants, as well as soil pollution with oils and residues of generator waste, cooling water and generator washing, as well as Loud sounds and noise produced by these generators of the large numbers from generators, besides all these things the high voices and loud noise spread of pollutants, whether in the air or soil of the city of Baghdad through the fumes and smoke emitted by the generators.